Entangled risks : knowledge co-production with sanitation workers to address current and future challenges of handling menstrual waste in informal settlements in Kenya - Dickin, Sarah; Gabrielsson, Sara; Rutto, Collins; Tatani, Priscilla; Okwaro, Neville (Health and Place, 2025)
This paper reports on the challenges of handling menstrual waste in informal settlements in Kisumu, Kenya, and the emerging conflicts between reducing the use of these ‘complicated plastics’ and ensuring human health and dignity. To investigate these interconnections, we draw on a survey conducted among sanitation workers conducting manual pit emptying. We then conducted a knowledge co-production workshop including generating maps showing flows of menstrual waste around Kisumu. The maps were used as the basis for a discussion of desirable futures in the context of waste and sanitation adapted from the Three Horizons methodology. Findings indicated that sanitation workers deal with large quantities of menstrual waste when conducting their day-to-day work, which produces a range of health, environmental, and social risks that are difficult to mitigate. Men were more likely than women workers to be unregistered, producing additional health and social risks due to this form of work often being conducted at night. Maps of waste flows in Kisumu showed very different realities among sanitation workers compared with other stakeholder groups such as government officials. When considering desirable waste futures, government and civil society stakeholders were in favour of an aspirational ‘zero waste’ future where plastic products are phased out in favour of reusable or biodegradable products. This was in tension with the future vision of sanitation workers who do not want to reduce waste, which is their main livelihood, and preferred better managed waste streams that reduced their risks and improved their standing in the community. These findings highlight conflicting priorities among stakeholders when addressing taboo waste streams such as menstrual waste, and the challenges of focusing on aspirational sustainability transitions that may harm socially marginalized groups.